Adaptive Strategies of Madrasah in Implementing The National Curriculum and Madrasah Operational Curriculum: Strategi Adaptif Madrasah Dalam Implementasi Kurikulum Nasional dan Kurikulum Operasional Madrasah - Hakim, Ilham Rahman; Unnajjah, Shifaun; Rahman, Ahmad Syaeful (CV. Media Publikasi Profesional, 2024)
This study aims to examine the implementation of the national curriculum and Madrasah Operational Curriculum (KOM) in an integrated manner at Madrasah Aliyah Swasta (MAS) Manbaul Huda, Bandung. This research is important to fill the void of studies on the integration strategy of general and religious curriculum in the context of madrasah, which is still limited. The method used is a qualitative approach with data collection techniques through participatory observation and curriculum documentation. Data were analysed thematically to identify implementation patterns and curriculum adaptation strategies. The main findings show that this madrasah integrates the National Curriculum, the Ministry of Religious Affairs Curriculum, and the Islamic Association (Persis) Curriculum to create a balance between academic achievement and religious character building. The Madrasah Operational Curriculum (KOM) is developed in a participatory and contextualised manner as an adaptive instrument to translate national policies into local practices. The implication of this research shows that the strategy of integration and flexibility in the preparation of KOM can be an innovative model for religious education institutions in facing the challenges of 21st century education. The originality of this research lies in the combination of three curricula that are rarely studied simultaneously as well as the emphasis on the participatory approach in the preparation of KOM, which makes a conceptual and practical contribution to the development of a value and competency-based madrasah curriculum.